The epidemiology of burns in a tertiary care center of Rajasthan - Khushalani, Asha; Srivastava, Sunil (International Surgery Journal, 2023)
Background: The aim of the present study is to determine the epidemiological pattern and outcome of burn injuries in a tertiary care centre of Rajasthan so that effective evidence based burn prevention programs can be generated and strong burn emergency health system can be established. Methods: This study includes retrospective data analysis of patients conducted over 2 years from January 2020 to December 2021 at burns and plastic surgery department of Sawai Man Singh (SMS) Hospital Jaipur situated in Rajasthan. Results: Total patients managed in SMS hospital were 2007 in 2 years. 65% were males and 35% were females. Most commonly affected age group was 25-39 years with 29% patients. Flame burns was most common mode with 49.6% cases among all age groups and both genders. Median TBSA was 35% as per this study. 37% patients were operated in same admission and definitive reconstruction was done. Mortality was there in 26.7% cases. Conclusions: Our study addresses the need of not only increasing the expenditure over prevention and education programs but also developing resources to improve the survival of burn patients in Rajasthan state. This study may contribute to establishment of strong infrastructure to prevent and treat severe burn injuries.